2019
DOI: 10.1177/1367006918819867
|View full text |Cite
|
Sign up to set email alerts
|

Input and literacy effects in simultaneous and sequential bilinguals: The performance of Albanian–Greek-speaking children in sentence repetition

Abstract: Aim: The present study examines input and literacy effects in simultaneous and sequential bilinguals with the aim of (a) investigating the differences between bilingual and monolingual populations and (b) disentangling the individual contribution of different factors in bilingual syntactic abilities. Methodology: A sentence repetition task (SRT) in Greek with eight structures (Subject Verb Object [SVO], negative clauses, clitic structures, complement clauses, coordinated sentences, adverbial clauses, wh-questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 64 publications
9
29
1
Order By: Relevance
“…Starting with the early life language practices, VAS was reported as the home language during childhood by L1VAS-L2GR bilinguals and 2L1s bilinguals but only by 25% of L1GR-L2VAS bilinguals with an overall very late exposure to the heritage language. The impact on language development due to variations in the amount of language input has been similarly documented in earlier work (Jia and Fuse 2007, Thordardottir 2011, Kaltsa et al 2020 and the use of the minority language as the home language has been associated with positive language outcomes as in our study (De Houwer 2007, La Morgia 2011. It is also important to note that all participants attended schools using only the majority language for instruction, namely, Greek, and only L1VAS-L2GR and 2L1s bilinguals would use VAS during recess to interact with peers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Starting with the early life language practices, VAS was reported as the home language during childhood by L1VAS-L2GR bilinguals and 2L1s bilinguals but only by 25% of L1GR-L2VAS bilinguals with an overall very late exposure to the heritage language. The impact on language development due to variations in the amount of language input has been similarly documented in earlier work (Jia and Fuse 2007, Thordardottir 2011, Kaltsa et al 2020 and the use of the minority language as the home language has been associated with positive language outcomes as in our study (De Houwer 2007, La Morgia 2011. It is also important to note that all participants attended schools using only the majority language for instruction, namely, Greek, and only L1VAS-L2GR and 2L1s bilinguals would use VAS during recess to interact with peers.…”
Section: Discussionsupporting
confidence: 86%
“…With regard to language input, the literature has shown that measures of input quantity have been employed to explain variation in several grammatical phenomena (Gathercole 2002a, 2002b, 2002c, Montrul and Potowski 2007, Unsworth et al 2014, Prentza et al 2019 or in the overall development of grammatical abilities (Jia and Fuse 2007, Chondrogianni and Marinis 2011, Thordardottir 2011, Kaltsa et al 2020. Recent research has also interestingly pointed out the positive effect of the quality of input in bilingual development as this was measured in terms of biliteracy exposure (Oller and Eilers 2002, Gathercole and Thomas 2009, Crago and Genesee 2011, Prentza et al 2019, Kaltsa et al 2020. Given that VA does not have a written from, literacy measures in our study considered literacy practices and schooling in Greek as well as any other languages that our participants used regularly.…”
Section: The Variety Of Va In the Community Of Sirrakomentioning
confidence: 99%
“…Regarding home literacy practices in particular, Prevoo et al (2014) found that reading in Dutch increased the Dutch vocabulary of Turkish–Dutch 5- and 6-year-olds. Kaltsa et al (2019) found that language and frequency of early and current home literacy practices in Greek had a positive impact on 8- to 10-year-old Albanian children’s syntactic abilities in their Greek L2.…”
Section: Language Environment and Bilingual Developmentmentioning
confidence: 99%
“…In the Canadian context, economic immigrants undergo a separate selection process from refugees: the former is a competitive process based on skills, education, and resources and the latter is a process based on humanitarian concerns. Furthermore, the bulk of research on language environment and bilingual development has been conducted with young children, mainly 3-8 years old, (e.g., Pham & Tipton, 2018;Place & Hoff, 2016;Prevoo et al, 2014;Sorenson Duncan & Paradis, 2020a) and research with older bilingual children and youth focuses mainly on those with longer residency and who have had most or all their education in the host country (e.g., Bayram et al, 2017;Flores, Santos, Jesus, & Marques, 2017;Kaltsa, Prentza, & Tsimpli, 2019; except see Jia &Aaronson, 2003 andJia &Fuse, 2007). Syrian families have recently migrated to Canada as refugees with children and youth of various ages.…”
mentioning
confidence: 99%
“…The child questionnaires were adapted from previous studies with bilinguals by Kaltsa et al (2019) and Rothou and Tsimpli (2017). Regarding bi/multilingualism, children were asked which languages were spoken at home by their parents, siblings, or other relatives and best friends-and in which languages they use to respond.…”
Section: Methodsmentioning
confidence: 99%